2012
DOI: 10.4238/2012.october.25.1
|View full text |Cite
|
Sign up to set email alerts
|

Does copper stress lead to spindle misposition-dependent cell cycle arrest?

Abstract: ABSTRACT. Because of its specific electrochemical properties, copper is an essential heavy metal for living organisms. As with other heavy metals, high levels can provoke damage. We examined gene expression under copper stress in wild-type fission yeast (Schizosaccharomyces pombe) through differential display. After the EC 50 concentration of CuSO 4 was determined as 50 µM, total RNA was isolated from cells treated or not with copper. The expression level of SPCC1682.13, ppk1, SPBC2F12.05c, and adg2 genes incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, copper can engage in detrimental chemical reactions or compete with other metal ions at enzyme-active sites, due to its ability to lose or gain a single electron [2]. It has also been reported that excess copper may cause cell-cycle misregulation [3]. It is therefore critical that cells use tightly regulated homoeostatic mechanisms to acquire sufficient amounts of copper, while at the same time preventing its accumulation to cytotoxic levels.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, copper can engage in detrimental chemical reactions or compete with other metal ions at enzyme-active sites, due to its ability to lose or gain a single electron [2]. It has also been reported that excess copper may cause cell-cycle misregulation [3]. It is therefore critical that cells use tightly regulated homoeostatic mechanisms to acquire sufficient amounts of copper, while at the same time preventing its accumulation to cytotoxic levels.…”
Section: Introductionmentioning
confidence: 99%